T Cell Repertoire Maturation Induced by Persistent and Latent Viral Infection Is Insufficient to Induce Costimulation Blockade Resistant Organ Allograft Rejection in Mice - Espinosa, Jaclyn R.; Mou, Danny; Adams, Bartley W.; DiBernardo, Louis R.; MacDonald, Andrea L.; McRae, MacKenzie; Miller, Allison N.; Song, Mingqing; Stempora, Linda L.; Wang, Jun; Iwakoshi, Neal N.; Kirk, Allan D. (Frontiers in Immunology, 2018)
CD28:CD80/86 pathway costimulation blockade (CoB) with the CD80/86-specific fusion protein CTLA4-Ig prevents T cell-mediated allograft rejection in mice. However, in humans, transplantation with CoB has been hampered by CoB resistant rejection (CoBRR). CoBRR has been attributed in part to pathogen-driven T cell repertoire maturation and resultant heterologous alloreactive memory. This has been demonstrated experimentally in mice. However, prior murine models have used viral pathogens, CoB regimens, graft types and/or antigen systems atypically encountered clinically. We therefore sought to explore whether CoBRR would emerge in a model of virus-induced memory differentiation designed to more closely mimic clinical conditions. Specifically, we examined mouse homologues of clinically prevalent viruses including murine polyomavirus, cytomegalovirus, and gammaherpesvirus 68 in the presence of clinically relevant maintenance CoB regimens using a fully MHC mismatched, vascularized allograft model. Infected mice developed a significant, sustained increase in effector memory T cells consistent with that seen in humans, but neither developed heterologous alloreactivity nor rejected primarily vascularized heterotopic heart transplants at an increased rate compared to uninfected mice. These results indicate that memory acquisition alone is insufficient to provoke CoBRR, and suggest that knowledge of prior latent or persistent viral infection may have limited utility in anticipating heterologous CoB-resistant alloimmunity.